2B4, the natural killer and T cell immunoglobulin superfamily surface protein, is a ligand for CD48. - Brown, M; Boles, K; Van Der Merwe, P; Kumar, V; Mathew, P; Barclay, A (1998)
2B4 is a cell surface glycoprotein related to CD2 and implicated in the regulation of natural killer and T lymphocyte function. A recombinant protein containing the extracellular region of mouse (m)2B4 attached to avidin-coated fluorescent beads bound to rodent cells, and binding was completely blocked by CD48 monoclonal antibodies (mAbs). Using surface plasmon resonance, we showed that purified soluble mCD48 bound m2B4 with a six- to ninefold higher affinity (Kd approximately 16 microM at 37 degreesC) than its other ligand, CD2. Human CD48 bound human 2B4 with a similar affinity (Kd approximately 8 microM). The finding of an additional ligand for CD48 provides an explanation for distinct functional effects observed on perturbing CD2 and CD48 with mAbs or by genetic manipulation.